Instilling the Value of Local Wisdom in Learning the History of the Subject of Islamic Development in Indonesia in Class X Social Studies Students at SMA Negeri 1 Pamotan - Afiqoh, Novianan; Atmaja, Hamdan Tri; Saraswati, Ufi (Indonesian Journal of History Education, 2021)
Education teaches the understanding of teaching materials and shapes attitudes and the media to preserve the local culture. The cultivation of local wisdom is necessary because students can better understand and love the culture they have. Education teaches the understanding of teaching materials and shapes attitudes and the media to preserve the local culture. The cultivation of local wisdom is necessary because students can better understand and love the culture they have. This research employs a qualitative method with a narrative approach. Informants in this research are history teachers and students of SMA Negeri 1 Pamotan. The techniques for collecting data are observation, interview, and documentation. To test data validity, this research uses data technique triangulation and source triangulation. The data analysis technique is interaction analysis, which consists of data collection, reduction, presentation, and conclusions. The results showed that 1) regarding the cultivation of local wisdom values through historical learning, the teachers only develop their knowledge related to local culture. Local wisdom is given more attention in school activities. 2) The implementation of the values of local wisdom is running well. The values of local wisdom include ethics, aesthetics, religion, and society.